The Impact of Corporate Social Responsibility on Brand Loyalty: Evidence from Ghana - Salifu, Shaibu; Saini, Yvonne K.; Moyo, Bhekinkosi (International Journal Labs, 2023)
Background: Corporate social responsibility has continuously achieved recognition as an active and well-organized marketing strategy in the recent years, but gaps still exist on its understanding and impact on brand loyalty. Aim: This paper examines the impact of corporate social responsibility on brand loyalty. Method: The authors applied descriptive statistics to examine the impact of Corporate social responsibility on brand loyalty of telecommunication industry in Ghana. Structured questionnaires were used to collect data from 600 customers of telecommunication companies in Ghana. The field data was analysed according to inferential and descriptive statistics. Findings: The study found that ethical and philanthropic dimensions of corporate social responsibility have significant impact on brand loyalty of telecommunication industry in Ghana. The findings have implications on telecommunication companies in Ghana and make significant contribution to academia.